Determination Superoxide Dismutase and Glutathione Levels in Serum of Patients with Diabetic Foot Infection in Karbala City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Diabetic foot infections (DFIs) are identified as localized purulence or inflammation that appears at the site beneath the malleoli in a diabetic patient. The goal of this study was to measure the levels of glutathione (GSH) and superoxide dismutase (SOD) in healthy people in Karbala city as well as in patients with type 2 diabetes mellitus who had or did not have diabetic foot ulcers. Materials and Methods:This study involved 120 participants ranging in age from 35 to 75 years, and was conducted at the Imam Al-Hassan Center for Endocrinology and Diabetes in Karbala, Iraq. To seperate the serum, five milliliters of the participants' blood were collected, put within gel tubes, and spun at 4000 xg in a cooled centrifuge. The serum was stored at -20˚C in Eppendorf tubes prior to utilizing it in determination of SOD and GSH levels.Results:  Superoxide dismutase (SOD) activity mean levels in DFI group where the result from patient were significantly lower (241.4±35.61) (U / L) (p≤0.001) than in diabetic patients and healthy individuals. Similarly, glutathione (GSH) mean levels in DFI group patients were lower than in diabetic patients and healthy individuals (26.586±2.77) µmole/ml (p≤0.001).Conclusion: These results imply that diabetic foot infections may be influenced by decreased antioxidant levels. This suggests that these antioxidants may be used as possible markers to diabetic those who are more vulnerable.